Study of neutral point clamped multilevel inverter with SVPWM - Lyu, Yuansen (2018)
Inverters are widely implemented in power system and electrical industry, such as renewable generation and auto-manufacturing. In recent years, an increasing amount of research attention is given to the design and development of multilevel inverters. Generally, multilevel inverters have better harmonic performance than two-level inverters. This report studies the space vector modulation strategy of neutral point clamped (NPC) three level inverter. In the first part of this report, the background of multilevel inverters is introduced. In the second part, the working principle of NPC inverter and the algorithm of space vector pulse width modulation (SVPWM) is demonstrated. Then, simulations of NPC inverter with SVPWM are conducted in MATLAB/SIMULINK environment, and the results are presented. Eventually, the results are discussed and the conclusions are drawn.